THE USE OF SOCIAL MEDIA AS HOSPITAL MARKETING TOOL - Arif, Umi Fikria; Darmawan, Ede Surya (Proceedings of the International Conference on Applied Science and Health, 2019)
Methods: This study was conducted in a systematic review by searching for articles and journals related to social media and hospital marketing. Literature search through the online database from University of Indonesia online library such as Scopus, Jstor, Ebsco, Proquest and Wiley on January 3th, 2019. The criteria of references are the use of social media in hospitals published within the year of 2009 to 2018 and can be accessed openly. Results: The search returned 21155 articles, of which only 4 studies were included in the systematic review. The results of the journals investigation showed that 51% - 99.41% of hospitals used social media. The average number of platforms used by a hospital in the sample was 3.3. About 71.8% updated their pages in the past 30 days, and 89.2% provided online interactions. There are significant correlations for hospitals' reputation score and total points with the number of social media followers. Conclusions: Many hospitals now use multiple social media platforms. The use of social media is affecting hospital's reputation. And because there is a high level of trust and sharing in social media communities, social media can be used as an effective tool for hospital marketing. To which extent the social media is still effective for marketing needs future studies regarding each country health regulations.